2020
DOI: 10.29238/teknolabjournal.v9i1.223
|View full text |Cite
|
Sign up to set email alerts
|

Human immune response to SARS-CoV-2 infection

Abstract: COVID-19 is an acute respiratory infection caused by a new type of Coronavirus, SARS-CoV-2, which first appeared in Wuhan, China in December 2019. COVID-19 then became a pandemic in various countries in early 2020. In this article it contains review that discusses the immune response in humans due to SARS-CoV-2 infection, using the narrative literature review method, a total of 36 articles (6 from Elsevier, 24 from PMC, and 6 from Springer). It is known that the pathogenesis of COVID-19 and the manufacture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Several studies have reported that SARS-CoV-2 binds to angiotensin converting enzyme 2 (ACE2) receptor on the host cell. The receptor played a key role in viral entry mechanism and related pathogenesis 7,8 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that SARS-CoV-2 binds to angiotensin converting enzyme 2 (ACE2) receptor on the host cell. The receptor played a key role in viral entry mechanism and related pathogenesis 7,8 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%